Shinji takahashi and the mark of the coatl eaudiobook - Kagawa, Julie (Disney Hyperion, 2022)
The first book in a globe-trotting middle-grade adventure, Shinji Takahashi and the Mark of the Coatl combines high-tech wizardry, old-world legends and a little bit of magic from the internationally renowned best-selling author, Julie Kagawa. Shinji Takahashi is just an ordinary kid. An ordinary homeschooled smart-alecky orphan kid being raised by his globe-trotting aunt Yui. But when a magical guardian decides to use him as a conduit to awaken its power, Shinji's life takes a turn for the anything-but-ordinary. Captured by the menacing Hightower Corporation, which is bent on using the guardian's magic for its own nefarious purposes, Shinji must team up with a brilliant young tech whiz named Lucy and her robot mouse, Tinker, in order to escape. Together the two turn to the venerable Society of Explorers and Adventurers and its ragtag cast of spelunkers, hackers, mapmakers, pilots, and mythology experts (among other things) to return the guardian to its rightful home and release Shinji from its magic—which seems to be draining his life force. Time is ticking, the Hightower Corporation is hot on their tail, and success or failure might depend on one small thing—Shinji finally coming around to the belief that he is anything but ordinary. Based on the Society of Explorers and Adventurers lore that exist across the Walt Disney Parks, Shinji Takahashi and the Mark of the Coatl is the first book in an all-new action-adventure series that brings S.E.A. into the twenty-first century through a blend of science and magic, and a focus on two young characters on an epic journey through time and place.